Evaluasi Dampak Kebijakan Revitalisasi Pasar Sukawati, Kabupaten Gianyar - A. A Istri Saraswati; I Putu Dharmanu Yudharta; I Dewa Ayu Putri Wirantari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Revitalization of traditional markets is a manifestation of the commitment of the Ministry of Trade of the Republic of Indonesia in efforts to improve the economy through development, empowerment, and then improving the quality of management in traditional markets as an effort to increase the competitiveness of traditional markets. The purpose of this study is to determine and examine the impact of the traditional market revitalization policy on Sukawati Market, because Sukawati Market is one of the markets with a high level of tourism productivity in Gianyar Regency. This study uses Qualitative methods, as well as the Policy Evaluation theory according to William N. Dunn (2003). This study found that the Evaluation of the Impact of the Sukawati Market Revitalization Policy has not achieved optimal results in all policy evaluation indicators, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The suboptimal revitalization policy at Sukawati Market as an effort to increase competitiveness in order to improve the welfare of traders is influenced by several things, namely human resource capacity, changes in infrastructure, and changes in market function after revitalization. The recommendations in this study are increasing human resource capacity, dissemination of information and promotion, and improving market governance.